Study on Soil Stabilization Using Rice Husk Ash and Cement In Marshy Soils (International Journal of Innovative Research in Computer Science & Technology, 2022)
The current study was conducted on  marshy soils found at Rakh Arth Bemina in Srinagar,  J&K,India with the goal of quantifying the effect of rice husk  ash and cement on the soil's dry density, optimum moisture  content and shear strength. The tests were performed on the  original soil sample first, followed by the same tests on the  other three samples with Rice Husk Ash(RHA) contents of  10%, 18%, and 22%, respectively, and each containing 8%  Cement(C). When 18 percent RHA was used, the goal of  increasing optimum moisture content and decreasing  maximum dry density was met. As compared to the original  sample, the maximum shear strength got increased by 14.8%.  Hence,the optimal RHA content is 18%. As a result, rice husk  ash combined with a small amount of cement can be a better  stabiliser for marshy soils, preventing failure and increasing  strength.
Keywords: Soil stabilization; Rice Husk Ash; Cement; Optimum Moisture Content; Shear strength